Analyzed Lexicon in Legong Mahawidya Dance Movement: A Descriptive Qualitative Study - Anggarawati, Ni Made Wita (International Journal of Language and Literature, 2022)
Language has an important role in preserving culture, because language is the key to communication. The research was conducted at the Pancer Langit Art Studio. The proposed research focus on the lexicons found in the motions and clothing of the Legong Mahawidya dance. Informants in this study are people who can perform this dance and the choreographer. This study used a descriptive qualitative approach. This study aims to identify the lexicon in Mahawidya Legong Dance. The data obtained through interviews with choreographers and dancers as informants in this study. Thirty-three (33) lexicon are found in the movemnet of Legong Mahawidya Dance. Not all lexicons in the movement have cultural meaning. Preserving Balinese culture, especially in language and art, is the responsibility of the Balinese people. By keeping the language, using the language continuously and understanding the language, the Balinese culture will be preserved and not extinct.